Protective effect of Col003 on the blood-brain barrier after cerebral ischemia-reperfusion injury in rats - XIE Yuliang; ZHOU Kejian; DENG Mengyu; XIE Xiaoyun; LIANG Tingting; LI Haoying; LIU Jingli (Guangxi Yike Daxue xuebao)
Objective To investigate the protective effect of Col003, an inhibitor of heat shock protein 47 (HSP47) on the blood-brain barrier (BBB) after cerebral ischemia-reperfusion injury in rats and its possible mechanism. Methods The rats were randomly divided into sham group, model group, butylphthalide group, and Col003 group. The middle cerebral artery occlusion (MCAO) model in rats was constructed using the suture occlusion method to simulate cerebral ischemia-reperfusion injury. After removing the suture, the rats in the butylphthalide group were intraperitoneally injected with butylphthalide (5 mg/kg). The rats in the Col003 group were injected with Col003 (50 μmol/L) through the tail vein, and the frequency and duration of administration of both drugs were once a day for 3 consecutive days. In the sham group, only the common carotid artery was isolated. Western blotting was used to detect the expression level of HSP47 in the brain tissues of rats after cerebral ischemia-reperfusion injury. The degree of brain dysfunction and BBB damage was assessed using TTC staining, neurological motor function scores, and Evans blue permeability assays. The effects of Col003 on endothelialmesenchymal transformation (EndMT) induced by cerebral ischemia-reperfusion in rats were evaluated by detecting the expression of tight junction proteins (ZO-1, Occludin, Claudin5) and mesenchymal marker proteins (α-SMA, Collagen I) in rat brain tissues by using western blotting, so as to further explore the possible mechanism of Col003 affecting BBB injury after cerebral ischemia-reperfusion in rats. Results At 24 h and 72 h after cerebral ischemia-reperfusion, the expression level of HSP47 in the brain tissue of rats was significantly higher than that in the sham group (P < 0.0001). Compared with the model group, the neurological function scores (P < 0.05) and motor function scores (P < 0.01) of MCAO rats in butylphthalide group and Col003 group were significantly improved, the cerebral infarction area was significantly reduced (P < 0.0001), and the Evans blue permeability was significantly decreased (P < 0.0001). Compared with the model group, the expression of tight junction protein in the brain tissue of Col003 group was significantly increased (P < 0.01), and the expression of mesenchymal marker protein was significantly decreased (all P < 0.01). Conclusion Col003 can improve BBB injury after cerebral ischemia-reperfusion, and has a protective effect on BBB. Its protective effect on BBB may be achieved by inhibiting EndMT.